Planning for a Microhydro Power Plant (PLTMH) in Raja Jaya Village, Penukal District, Penukal Abab Lematang Ilir Regency - Dimas Kasmoro; Emidiana Emidiana; Yudi Irwansi; M.Saleh Al amin (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2024)
The need for electrical energy is increasing, especially in rural areas, so building an environmentally friendly energy power plant such as a micro hydro generator can be used to produce electrical energy. This PLTMH planning aims to help the community produce environmentally friendly electrical energy and overcome frequent power outages. The research discusses determining the type of turbine, water discharge, turbine power and generator power at (PLTMH). The water discharge (Q) value of 2.67 m3/sec is the water discharge during the rainy season. From the calculation results, it can generate 25.65 kW of electrical energy, the type of turbine used is an open flume propeller type turbine, the planning of a micro-hydro power plant with a turbine power capacity of 60 kW and a generator of 50 kW greatly influences the power that will be produced by the turbine, which This means that the greater the water discharge, the greater the power generated by the turbine, conversely, if the water discharge is small, the power produced by the turbine is relatively small.